(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In general, one of the global issues that affects not only young people, but also young people around the world, is the social network, its use, benefits and harms, effects and consequences. This article describes both the proper way of life of the youth and their rational use of social networks as a guide. The article presents a number of controversial views on the history, timing and popularity of social media.